Brief instrument for direct complex functionality assessment: a new ecological tool - Holz, Maila Rossato; Kochhann, Renata; da Silva, Patrícia Ferreira; Wilson, Maximiliano A.; Fonseca, Rochele Paz (Frontiers in Neuroscience, 2023)
Background The Direct Assessment of Functional Status (DAFS) is the only instrument validated in Brazil that assesses functionality directly with the patient. However, this clinical tool takes a long time to be administered. This limits its use in hospitals and outpatient clinics that require brief assessment instruments. Additionally, we need to count with a direct assessment because the number of older adults living alone is increasing and we thus lack reliable informants. Objective This study aimed to present the development and content validity evidence of a direct complex functionality test for older adults, the Brief Instrument for Direct Functionality Assessment (BIDFA). Method A total sample of 30 older adults and eight expert judges took part in the study stages. The BIDFA construction stages were: (1) literature review of functionality instruments; (2) development of seven ecological tasks to evaluate the performance of daily complex activities with the older adults; (3) content analysis by eight expert judges; (4) pilot study with 30 older adults; (5) the ecological analysis of items; (6) focus group analysis; and (7) final version of the BIDFA. Results The BIDFA had evidence of content validity with an agreement index of 96.5%. The final version of BIDFA was left with six domains of complex functionality divided into semantic memory and time orientation; shopping skills; executive attention, math and finance skills; organization; planning and procedural memory; and problem-solving. The complex functionality score by BIDFA ranges from 0 to 100 points. Conclusion The BIDFA was found to have good content validity by the expert judges and by the ecological analysis of the items by the older adults. The new instrument is expected to help assess the functional status of older adults, in an abbreviated context including complex functionality demands, with a wider range of total and subdomain scores.